Demands of Project-based Teaching Supported by the Evaluation Directed to the Learning of Graduate Students in the Arabic Language Department at University of Tabuk from the point of view of the Academic Staff - Alomrani, Layla Falah Salem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the demands of project-based teaching supported by the evaluation directed to the learning of graduate students in the Arabic Language Department from the viewpoint of the Academic Staff at the University of Tabuk. To achieve this, the researcher used the descriptive analytical approach by applying a questionnaire that included (60) items distributed to a sample of (41) all the academic staff in the Arabic Language Department at University of Tabuk. The results were as follows: the overall instrument received a mathematical average of (4.09 out of 5) with a (large) approval score. According to the main demands, project-based teaching planning demands received the highest average of 4.13, followed by project-based implementation demands (4.11).Finally, the demands for evaluating and managing project-based teaching results are average (4.04), all with a approval rating (large), and it has been shown that there are no statistically significant differences at the (≥α0.05) level of indication scoring between the averages of the sample’s evaluation of the claims due to variables (sex, academic rank, qualification type, training). The statistically significant differences were attributable to the variable (years of experience) in the responses of the sample members to the demands of the implementation of project-based teaching for those with teaching experience (10 years and over). Based on the results, the researcher submitted a number of recommendations and proposals to strengthen the demands of project-based teaching supported by the evaluation for the learning of graduate students in the Arabic Language Department and all departments in the universities of the Kingdom of Saudi Arabia and all Arab universities.